Accuracy and reproducibility of conventional radiographic assessment and subtraction radiography in detecting demineralization in occlusal surfaces (2007)
Subjective interpretation of paired digital radiographic images viewed side by side to assess occlusal lesion progression, arrest or remineralization is difficult. The aim of this study was to compare the accuracy and reproducibility of a digital subtraction radiography technique and visual assessment of paired digital images in detecting changes in mineral content within occlusal cavities. Forty molar teeth with occlusal cavities were placed in arches and baseline digital radiographs taken. Nineteen teeth were randomly selected and had acid placed in the cavities and digital images taken after 3, 6, 12, 18 and 24 h of acid exposure. Paired baseline images and those taken at the various time intervals were examined side by side and assessed for demineralization by five examiners. Subtraction images prepared from the paired images were assessed in the same way. One fifth of the images were re-examined to determine intra-examiner reproducibility. After 12 h or longer the diagnostic accuracy (mean area under the ROC curve = 0.92–0.98 for subtraction radiography), intra-examiner and inter-examiner reproducibility for detection of demineralization from the subtraction images was significantly better than viewing the paired images side by side (p < 0.01). The subtraction radiography system used was found to be more accurate and reproducible than visual assessment of paired digital images. As such the technique shows promise for monitoring occlusal lesion progression in clinical studies.